O impacto do salário mínino sobre o desemprego no Brasil - Lucas, Kézia de Sousa (2006)
The dissertation presents a study on the impact of the minimum wage on the rate of unemployment in Brazil between 2000 and 2005. The methodology applied is based on "difference-in-differences", and the source of data is the Pesquisa Mensal de Emprego (PME), published by the Brazilian Institute of Geography and Statistic (IBGE). We work with two "Groups of Treatment", the metropolitan areas of Rio de Janeiro and Porto Alegre and a "Group of Control", with the remaining metropolitan areas of Brazil (Belo Horizonte, Salvador, Recife and Sao Paulo). In general it is verified that the minimum wage doesn't impact the unemployment rate. However there is an exception in the wage changes occurred in Rio de Janeiro in January of 2002 and January of 2004. In these cases, it is verified that an increase of the minimum wage increases the unemployment rate. Beyond this result one also evidences that an increase of the minimum wage reduces the unemployment rate for people between 15 and 17 years old in January of 2005.